Biotechnology for promising secondary metabolites of cyanobacteria (Experimental biology, 2015)
The review describes the available diversity toxins of cyanobacteria and their prospects for biotechnology. Particular attention is paid to types of toxins, representing on the one hand a danger to humans and animals, and at the same time interesting for medicine and biotechnology as a source of various pharmaceuticals.
Keywords: cyanobacteria; Microcystis aeruginosa; Microcystis aeruginosa Kutz; Nostoc rivulare; toxins; hepatotoxins; cytotoxicity; microcystins